2021
DOI: 10.3390/vaccines9101097
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccinations: A Comprehensive Review of Their Safety and Efficacy in Special Populations

Abstract: COVID-19 has been spreading worldwide since late 2019. There is no definitive cure to date. Global vaccination programs are urgently required to confer herd immunity, reducing the incidence of COVID-19 infections and associated morbidity and mortality. However, a significant proportion of special populations are hesitant to receive vaccination due to their special conditions, namely, age (pediatrics and geriatrics), immunocompromised state, autoimmune diseases, chronic cardiovascular and pulmonary conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 156 publications
2
28
0
2
Order By: Relevance
“…Using an integrated psychosocial model informed by relevant theoretical and empirical work, the study findings indicated that both individual and social factors are critical determinants of vaccine hesitancy (own decision) as well as hesitancy when making decision for children's vaccination, but specific predictors differed. Adult vaccine hesitancy was driven by vaccination beliefs [i.e., necessity of the vaccine, vaccine benefits for self and wider community (moral norm)], social/peer influence (subjective norms) and living with people in poor health, which were in line with prior work [29,37,39,65].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Using an integrated psychosocial model informed by relevant theoretical and empirical work, the study findings indicated that both individual and social factors are critical determinants of vaccine hesitancy (own decision) as well as hesitancy when making decision for children's vaccination, but specific predictors differed. Adult vaccine hesitancy was driven by vaccination beliefs [i.e., necessity of the vaccine, vaccine benefits for self and wider community (moral norm)], social/peer influence (subjective norms) and living with people in poor health, which were in line with prior work [29,37,39,65].…”
Section: Discussionsupporting
confidence: 59%
“…As individuals in poor health are at higher risk for poor prognosis if infected with COVID-19 [65], their vulnerability could have invoked an increased sense of responsibility and accountability in people living with them, resulting in increased willingness to receive the vaccine. Relatedly, collective responsibility as reflected in moral norms was also shown to be associated with lower odds of hesitancy, consistent with prior work [29,66].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we must determine whether or not to administer the vaccine during the first trimester of the pregnancy or the second and third trimesters. The rationale behind second and third trimester vaccination can be the potential to pass antibodies from the mother to the fetus, thus causing passive immunity in the child after delivery [69,71]. It is now an important determination considering the clinical trials in children under five are ongoing, and the results are pending.…”
Section: Vaccination and Pregnancymentioning
confidence: 99%
“…Elderly and immunocompromised patients are at higher risk of mortality 1 . Among kidney transplant recipients the mortality rate was reported 10–40%, and the adjusted odds ratio for in‐patient death in kidney transplant recipients was 3.12 (95% confidence interval [CI] 2.323–4.36) 2–3 …”
Section: Introductionmentioning
confidence: 99%
“…1 Among kidney transplant recipients the mortality rate was reported 10-40%, and the adjusted odds ratio for in-patient death in kidney transplant recipients was 3.12 (95% confidence interval [CI] 2.323-4.36). [2][3] Effective vaccination raises anticipation to control the pandemic. Different vaccine platforms have been developed, including mRNA, viral vector, protein subunit, and whole-cell inactivated virus vaccines, with a wide range of reported efficacy in the general population.…”
Section: Introductionmentioning
confidence: 99%